A modified sodium vanadium fluorophosphate material, its preparation method and application

CN122576140APending Publication Date: 2026-08-14KUNMING UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610514456.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-04-17
Publication Date
2026-08-14

AI Technical Summary

Technical Problem

[0005]本发明的目的是针对以上所述现有技术中存在的正极材料在充放电循环过程中容量快速衰减、低稳定性和低活性等问题,提供一种改性氟磷酸钒钠(NVPF)材料,通过六偏磷酸钠的特异性配位与界面吸附双重作用,精准调控晶粒生长动力学,获得粒径均一、分散良好的纳米级NVPF材料,显著提升其作为钠离子电池正极的电化学性能及长循环稳定性

Benefits of technology

(1) 形貌调控机制创新:首次将六偏磷酸钠用于NVPF合成过程的晶体生长调控,利用其多磷酸根与钒离子的特异性螯合作用及界面吸附效应,实现了成核-生长动力学的精准调控,获得了粒径200-500nm、分散均匀的纳米级材料,显著缩短了钠离子扩散路径。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122576140A_ABST
    Figure CN122576140A_ABST
Patent Text Reader

Abstract

This invention discloses a modified sodium vanadium fluorophosphate material, its preparation method, and its applications. To address the technical problems of low conductivity and poor rate performance in existing sodium vanadium fluorophosphate materials, this invention employs a sodium hexametaphosphate-assisted hydrothermal method to construct an integrated preparation system of "surfactant regulation-hydrothermal crystallization." Sodium hexametaphosphate stabilizes the system and regulates the crystal nucleation rate by coordinating polyphosphate ions with the metal ions of the sodium vanadium fluorophosphate precursor. Simultaneously, it adsorbs at the crystal growth interface, inhibiting particle agglomeration and adjusting the crystal facet growth rate ratio through steric hindrance. The particle size of sodium vanadium fluorophosphate is continuously adjustable by controlling the amount of sodium hexametaphosphate added. The beneficial effects of this invention are: it effectively improves electrode mass transfer efficiency, synergistically enhances the electrochemical performance of sodium vanadium fluorophosphate materials, establishes a simple and efficient "one-step synthesis-performance optimization" technical solution, and provides a theoretical basis and experimental reference for the preparation and application of high-performance sodium vanadium fluorophosphate materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sodium-ion battery cathode material technology, specifically to a modified sodium vanadium fluorophosphate material, its preparation method and application, wherein the modification of sodium vanadium fluorophosphate crystal morphology and electrochemical performance is controlled by a hydrothermal method assisted by sodium hexametaphosphate (SHMP). Background Technology

[0002] The combustion of fossil fuels (mainly including oil, natural gas, and coal) is the biggest cause of severe climate change problems such as the greenhouse effect. Considering the non-renewable and polluting nature of fossil energy, the development of clean and renewable alternative energy sources has become an urgent need. Against this backdrop, solar and wind power have received widespread attention as clean energy sources, but their power generation is intermittent, requiring supporting energy storage systems. However, solar and wind power are constrained by weather conditions, resulting in intermittent and fluctuating power generation, making it difficult to achieve stable power supply. Therefore, developing efficient and economical large-scale energy storage technologies has become crucial. Lithium-ion batteries have been widely used due to their high energy density, long lifespan, and excellent overall performance. However, the uneven distribution and scarcity of lithium sources in the Earth's crust leads to the high cost of lithium-ion batteries. Sodium-ion batteries, with similar working principles to lithium-ion batteries (both being rocking chair batteries), have attracted widespread attention from researchers. Existing cathode material sodium vanadium fluorophosphate, due to its NASICON (sodium superionic conductor) structure, has become one of the popular research directions for sodium-ion cathode materials, but its poor intrinsic electronic conductivity limits further applications. Common methods for modifying sodium vanadium fluorophosphate (CNF) cathode materials include nanostructure design, elemental doping, and surface modification. The aim is to improve the material's electrical conductivity and enhance its electrochemical performance as a cathode material, resulting in superior electrochemical performance when used as a cathode in sodium-ion batteries.

[0003] Chinese invention patent application CN 108682855 A discloses a method for controllably preparing sodium vanadium fluorophosphate cathode material. The method involves mixing a sodium source, vanadium source, phosphoric acid source, fluorine source, and a chelating agent in deionized water to obtain a solution or suspension, which is then placed in a hydrothermal reactor for a hydrothermal reaction. The hydrothermal product is washed and dried, and the resulting powder is the sodium vanadium fluorophosphate cathode material or its precursor. The precursor is then heat-treated in a non-oxidizing atmosphere, and after cooling, the sodium vanadium fluorophosphate cathode material is obtained. This technical solution can controllably prepare sodium vanadium fluorophosphate cathode material with target morphology and particle size to improve its electronic and ionic conductivity, thereby improving its electrochemical performance, especially rate performance and cycle performance. However, this technical solution improves its electrochemical performance by carbon coating the sodium vanadium fluorophosphate conductive carbon material, which involves complex preparation steps. The resulting electrode material suffers from defects such as low discharge specific capacity, poor discharge performance, poor long-cycle stability, and low activity, which still need to be improved.

[0004] Therefore, there is an urgent need for a modified sodium vanadium fluorophosphate material and its preparation method, which can significantly improve electrode mass transfer efficiency and enhance the electrochemical performance and long-cycle stability of electrode materials. Summary of the Invention

[0005] The purpose of this invention is to address the problems of rapid capacity decay, low stability, and low activity of cathode materials in the prior art during charge-discharge cycles, and to provide a modified sodium vanadium fluorophosphate (NVPF) material. Through the dual effects of specific coordination and interfacial adsorption of sodium hexametaphosphate, the grain growth kinetics are precisely controlled to obtain a nanoscale NVPF material with uniform particle size and good dispersion, which significantly improves its electrochemical performance and long-cycle stability as a cathode material for sodium-ion batteries.

[0006] Another objective of this invention is to provide a method for preparing the modified sodium vanadium fluorophosphate material. The method utilizes sodium hexametaphosphate (SHMP) as a surfactant to assist in hydrothermal regulation of the growth of cathode material grains. By leveraging the dual effects of SHMP coordination and interfacial adsorption, the method induces the growth of material crystals, thereby precisely controlling the morphology of the cathode material and improving its electrochemical performance in battery applications. The process is simple, the conditions are mild, the controllability is strong, and it is easy to scale up production.

[0007] A third objective of this invention is to provide applications of the modified sodium vanadium fluorophosphate material, including its use in the preparation of carbon-coated composite materials, sodium-ion battery cathode materials, and sodium-ion batteries.

[0008] To achieve the above objectives, the present invention adopts the following technical solution: a sodium vanadium fluorophosphate material, comprising a sodium vanadium fluorophosphate matrix and sodium hexametaphosphate adsorbed on the surface of the sodium vanadium fluorophosphate matrix, wherein the mass ratio of sodium hexametaphosphate to the sodium vanadium fluorophosphate matrix is ​​1:(0.25-0.75).

[0009] The sodium hexametaphosphate is used to disperse and induce the growth of sodium vanadium fluorophosphate crystals.

[0010] Preferably, the sodium vanadium fluorophosphate matrix has the chemical formula Na3V2(PO4)2F3, an average particle size of 200-500 nm, and a specific surface area of ​​15-35 m². 2 ·g -1 .

[0011] The sodium vanadium fluorophosphate matrix is ​​composed of ammonium metavanadate, oxalic acid, anhydrous sodium dihydrogen phosphate, and sodium fluoride in a molar ratio of N. 偏钒酸铵 :N 草酸 :N 无水磷酸二氢钠 :N 氟化钠 Made with a ratio of 2:2:2:3.

[0012] The preparation method of the modified sodium vanadium fluorophosphate material includes the following steps: (1) Preparation of precursor: Ammonium metavanadate was dissolved in deionized water and stirred at 70-80℃ and 80-120 rpm for 20-30 min; oxalic acid was added and stirring was continued for 25-35 min to obtain a blue solution (vanadium oxalate oxychloride complex); anhydrous sodium dihydrogen phosphate and sodium fluoride were added and stirred for 0.8-1.2 h; sodium hexametaphosphate was added and stirring was continued for 0.8-1.2 h to obtain the precursor solution; (2) Hydrothermal reaction: The precursor solution obtained in step (1) is transferred to a reaction vessel with a polytetrafluoroethylene liner, and the temperature is raised to 170-180℃ for 9-10 h to obtain the reaction product; (3) Post-processing: The reaction product obtained in step (2) is centrifuged, washed, dried and ground, and then calcined at 540-560℃ for 6.5-7.5h in an argon mixed atmosphere containing 2vol% hydrogen to obtain modified sodium vanadium fluorophosphate material.

[0013] Preferably, the molar ratio of ammonium metavanadate, oxalic acid, anhydrous sodium dihydrogen phosphate, and sodium fluoride is N. 偏钒酸铵 :N 草酸 :N 无水磷酸二氢钠 :N 氟化钠 =2:2:2:3.

[0014] Preferably, the amount of sodium hexametaphosphate added in step (1) is such that the mass ratio of sodium hexametaphosphate to sodium vanadium fluorophosphate reaches 1:(0.25-0.75).

[0015] The sodium hexametaphosphate can also be prepared to a concentration of 0.05-0.2 g·mL. -1 A sodium hexametaphosphate aqueous solution is prepared to facilitate rapid and uniform mixing.

[0016] Preferably, in step (1), ammonium metavanadate is first dissolved in deionized water and stirred at 75 °C at 100 rpm for 25 min. Then oxalic acid is added and stirred at 75 °C for 30 min. Then anhydrous sodium dihydrogen phosphate and sodium fluoride are added and stirred for 1 hour. Then sodium hexametaphosphate is added and stirred for 1 hour.

[0017] Preferably, in step (2), the hydrothermal reaction conditions are: temperature 170℃ and time 9 h.

[0018] Preferably, the centrifugal cleaning in step (3) involves washing with anhydrous ethanol 2-3 times and then washing with deionized water 2-3 times; the drying is carried out at 85-95℃ for 11-13 hours; and the grinding is carried out in an agate mortar for 10-14 hours.

[0019] The mechanism of action of this invention is explained as follows: The polyphosphate group in the sodium hexametaphosphate molecule has a strong chelating ability and can bind with vanadium ions (VO2+) in the precursor solution.+ or V 3+ This process forms stable cyclic chelates, altering the morphology and concentration distribution of vanadium species in the solution, thereby affecting the nucleation rate of NVPF. Simultaneously, SHMP adsorbs onto the crystal nucleus surface, inhibiting grain aggregation through steric hindrance and electrostatic repulsion, and selectively adsorbs onto specific crystal faces, regulating the anisotropic growth rate, ultimately yielding nanoscale NVPF materials with uniform particle size and regular morphology. A suitable amount of SHMP remaining on the material surface can also act as a surface modifier to improve electrode / electrolyte interface compatibility. In contrast, this invention uses sodium hexametaphosphate (SHMP) as a surfactant for crystal facet selectivity regulation, resulting in a simpler preparation process and significantly improved electrochemical performance of the material.

[0020] A modified sodium vanadium fluorophosphate composite material includes the aforementioned modified sodium vanadium fluorophosphate material and a char-forming agent coated on its surface, wherein the mass content of the char-forming agent is 5-15%. The char-forming agent includes, but is not limited to, polyamide.

[0021] The preparation method of the modified sodium vanadium fluorophosphate composite material includes the following steps: (1) The modified sodium vanadium fluorophosphate material and the carbonizing agent are mixed at a mass ratio of 10:(0.5-1.5) and ball-milled for 8-14 hours to obtain a mixture; (2) After cleaning and drying the mixture obtained in step (1), it is sintered at 580-620℃ for 3.5-4.5h in an argon mixed atmosphere containing 2vol% hydrogen to obtain the modified sodium fluorophosphate composite material.

[0022] Preferably, the char-forming agent is at least one selected from polyamide, polypyrrole, polyaniline, sucrose, or citric acid.

[0023] Preferably, the ball milling conditions for step (1) are: rotation speed of 450 r / min and time of 12 h.

[0024] Preferably, the cleaning conditions for step (2) are as follows: the cleaning agent is a solvent that is miscible with the solvent and does not dissolve into carbon and sodium vanadium fluorophosphate; the drying conditions are: temperature of 90°C and time of 12 h; the sintering conditions are: temperature of 600°C and time of 4 h.

[0025] A sodium-ion battery cathode material includes the modified sodium vanadium fluorophosphate composite material, a conductive agent, and a binder, wherein the mass content of the modified sodium vanadium fluorophosphate composite material is 60-90%.

[0026] Preferably, the mass ratio of the modified sodium vanadium fluorophosphate composite material, the conductive agent, and the binder is (7-8):(1-2):(1-2).

[0027] Preferably, the conductive agent is conductive carbon black, Super P or Ketjen black, and the binder is polyvinylidene fluoride.

[0028] A sodium-ion battery includes a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the positive electrode comprises the above-mentioned sodium-ion battery positive electrode material.

[0029] The method for preparing the sodium-ion battery includes the following steps: (1) The modified sodium vanadium fluorophosphate composite material, conductive carbon black and polyvinylidene fluoride are weighed and added into an agate jar and dissolved in solvent N-methylpyrrolidone. The mixture is ball-milled at a speed of 300-400 r / min for 8-10 h. The ball-milled slurry is then coated onto aluminum foil and dried to evaporate the solvent, thus obtaining the positive electrode of the sodium-ion battery. (2) Subsequently, CR2032 button batteries were assembled in a glove box filled with argon gas, with water and oxygen values ​​both below 0.1 ppm. Glass fiber was used for the separator, and a mixed solvent system of EC / DMC / EMC (1:1:1, volume ratio) of 0.8-1.2 mol / L NaClO4 was used for the electrolyte. 1.5-2.5% (mass fraction) of FEC was added as an additive.

[0030] Preferably, in step (1), the ball milling speed is 350 r / min and the ball milling time is 9 h.

[0031] Preferably, in step (2), the electrolyte is a mixed solvent system of EC / DMC / EMC (1:1:1, volume ratio) of 1 mol / L NaClO4, with 2% (mass fraction) of FEC added as an additive.

[0032] Sodium-ion batteries prepared using the modified sodium vanadium fluorophosphate composite material can effectively improve the cycle discharge capacity and stability of NVPF by combining SHMP particle size control with carbon coating.

[0033] This invention utilizes a sodium hexametaphosphate-assisted hydrothermal method to prepare modified sodium vanadium fluorophosphate. The hydrothermal method employs low-temperature liquid-phase control, resulting in a simple process and a product with intact crystal structure and uniform particle size distribution. Sodium hexametaphosphate (SHMP) acts as both a dispersant and a special surfactant during the synthesis process. The addition of SHMP disperses crystal growth during the synthesis of Na3V2(PO4)2F3, effectively preventing the agglomeration of sodium vanadium fluorophosphate crystals, thus obtaining modified Na3V2(PO4)2F3 crystals with smaller particle size and better dispersion. Sodium vanadium fluorophosphate with added SHMP, as a cathode material for sodium-ion batteries, exhibits smaller particle size, superior rate performance, and long-cycle performance. Further coating the surface of this modified sodium vanadium fluorophosphate material with a carbon layer yields a modified sodium vanadium fluorophosphate composite material, which significantly improves both rate performance and long-cycle stability.

[0034] Compared with the prior art, the beneficial effects of the present invention are: (1) Innovation of morphology regulation mechanism: Sodium hexametaphosphate was used for the first time to regulate crystal growth in the NVPF synthesis process. By utilizing the specific chelation effect of its polyphosphate and vanadium ions and the interfacial adsorption effect, the nucleation-growth kinetics were precisely regulated, and nanoscale materials with a particle size of 200-500 nm and uniform dispersion were obtained, which significantly shortened the sodium ion diffusion path.

[0035] (2) Significantly improved electrochemical performance: The modified material with the optimal ratio (1:0.5) achieved a first-cycle discharge specific capacity of 106.4 mAh·g at a 0.5C rate. -1 Compared to the unmodified material (100.79 mAh·g), -1 The capacity retention rate was 96.9% after 100 cycles, which is 7.7 percentage points higher than that of the unmodified material (89.2%), demonstrating excellent structural stability and cycle life.

[0036] (3) Synergistic modification effect: After carbon coating, the SHMP-modified material has synergistic improvement in electronic conductivity and ion transport efficiency. While maintaining high capacity, the rate performance of the composite material is further improved.

[0037] (4) Simple and controllable process: The hydrothermal method has mild conditions, SHMP has good water solubility and is easy to disperse, and the post-processing process is conventional, making it suitable for large-scale production. Attached Figure Description

[0038] Figure 1 Here are the SEM images of the modified NVPF materials: (ac)B-NVPF, (df)S-NVPF-1, (gi)S-NVPF-2, (jl)S-NVPF-3; and the EDS elemental distribution map of (mq)S-NVPF-2. Figure 2 The modified NVPF materials with different SHMP addition amounts and the cycling performance of S-NVPF-2 at 0.5 C; Figure 3 These are the charge-discharge curves of S-NVPF-2 at 1 C; Figure 4 This is a comparison chart of the cycling performance of samples B-NVPF, S-NVPF-2, and S-NVPF@C at 0.5 C. Detailed Implementation

[0039] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with specific embodiments and accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0040] A sodium vanadium fluorophosphate material comprises a sodium vanadium fluorophosphate matrix and sodium hexametaphosphate adsorbed on the surface of the sodium vanadium fluorophosphate matrix. It is prepared by a low-temperature liquid-phase controlled assisted hydrothermal method. The mass ratio of sodium hexametaphosphate to the sodium vanadium fluorophosphate matrix is ​​1:0.25, 1:0.50, or 1:0.75. The sodium vanadium fluorophosphate matrix has the chemical formula Na3V2(PO4)2F3 (NVPF), an average particle size of 200-500 nm, and a specific surface area of ​​15-35 m². 2 ·g -1 .

[0041] The preparation method of the modified sodium vanadium fluorophosphate material includes the following steps: (1) Add 0.02 mol ammonium metavanadate to 150 mL of deionized water, heat to 75 °C in a water bath and stir at 100 rpm for 25 min; then add 0.02 mol oxalic acid and continue stirring for 30 min; then add 0.02 mol anhydrous sodium dihydrogen phosphate and 0.03 mol sodium fluoride and stir for 1 h; then add sodium hexametaphosphate powder in the above range and stir for 1 h. (2) The solution from step (1) was transferred to a reaction vessel with a polytetrafluoroethylene liner and reacted at the set temperature. After the reaction was completed, the reaction product was washed with anhydrous ethanol and deionized water respectively. Then the temperature was raised to 85 °C and dried for 12 h. The dried reaction product was calcined at 550 °C for 7 h in an argon mixed atmosphere containing 2 vol % hydrogen to obtain the modified sodium vanadium fluorophosphate material (S-NVPF).

[0042] The surface of the modified sodium vanadium fluorophosphate material was coated with carbon to obtain a modified sodium vanadium fluorophosphate composite material, which significantly improved both rate performance and long-cycle stability.

[0043] The preparation method of the modified sodium vanadium fluorophosphate composite material includes the following steps: (1) The modified sodium vanadium fluorophosphate material and the carbonizing agent (preferably polyamide, i.e. PA) are mixed at a mass ratio of 10:1, and the mixture is ball-milled at a speed of 450 r / min for 12 h. (2) The mixture obtained in step (1) was washed three times with anhydrous ethanol, then heated to 90 °C and dried for 12 h, and then sintered at 600 °C for 4 h in an argon mixed atmosphere containing 2 vol % hydrogen to obtain the modified sodium vanadium fluorophosphate composite material (S-NVPF@C).

[0044] The modified sodium vanadium fluorophosphate material (S-NVPF) and the modified sodium vanadium fluorophosphate composite material are used to prepare sodium-ion batteries. The preparation method of the sodium-ion battery includes the following steps: the modified sodium vanadium fluorophosphate material or the modified sodium vanadium fluorophosphate composite material, conductive carbon black, and polyvinylidene fluoride are weighed and added to an agate jar in a mass ratio of 7:2:1, and an appropriate amount of solvent N-methylpyrrolidone is added until the solid is completely dissolved. The mixture is ball-milled at 350 r / min for 9 hours. The ball-milled slurry is then coated onto aluminum foil, the solvent is evaporated, and the mixture is dried to obtain the positive electrode of the sodium-ion battery. The positive electrode is then assembled into a CR2032 type button battery in a glove box filled with argon gas, where the water and oxygen values ​​are both below 0.1 ppm. The separator is made of glass fiber, and the electrolyte is a mixed solvent system of EC / DMC / EMC (1:1:1, volume ratio) of 1 mol / L NaClO4, with 2% (mass fraction) FEC added as an additive. Example 1

[0045] A method for preparing modified sodium vanadium fluorophosphate material includes the following steps: 0.02 mol ammonium metavanadate is added to 150 mL of deionized water, and the mixture is heated to 75 °C in a water bath and stirred at 100 rpm for 25 min; 0.02 mol oxalic acid is added, and stirring is continued for 30 min; simultaneously, 0.02 mol anhydrous sodium dihydrogen phosphate and 0.03 mol sodium fluoride are added and stirred for 1 h; then, sodium hexametaphosphate powder is added at a mass ratio of 1:0.25 according to the theoretical yield of sodium hexametaphosphate to NVPF (i.e., the theoretical yield of pure phase Na3V2(PO4)2F3 obtained by the above ratio), and stirring is continued for 1 h to obtain a mixed solution; the above uniformly stirred mixed solution is transferred to a reaction vessel with a polytetrafluoroethylene liner, and the temperature is raised to 170 °C for 9 h; the reaction product is washed three times each with anhydrous ethanol and deionized water, and then dried at 85 °C for 12 h; the dried reaction product is then subjected to a reaction containing 2 vol Modified Na3V2(PO4)2F3 material (S-NVPF-1) was prepared by calcination at 550℃ for 7 h under a mixed atmosphere of hydrogen and argon. Example 2

[0046] A method for preparing modified sodium vanadium fluorophosphate material includes the following steps: 0.02 mol ammonium metavanadate is added to 150 mL of deionized water, and the mixture is heated to 75 °C in a water bath and stirred at 100 rpm for 25 min; 0.02 mol oxalic acid is added, and stirring continues for 30 min; simultaneously, 0.02 mol anhydrous sodium dihydrogen phosphate and 0.03 mol sodium fluoride are added and stirred for 1 h; then, sodium hexametaphosphate powder is added at a mass ratio of 1:0.5 (the theoretical yield of sodium hexametaphosphate to NVPF, i.e., the theoretical yield of pure phase Na3V2(PO4)2F3 obtained from the above ratio), and stirring continues for 1 h to obtain a mixed solution; the uniformly stirred mixed solution is transferred to a reaction vessel with a polytetrafluoroethylene liner and heated to 170 °C for 9 h; the reaction product is washed three times each with anhydrous ethanol and deionized water, and then dried at 85 °C for 12 h; the dried reaction product is then subjected to a reaction in a solution containing 2 vol Modified Na3V2(PO4)2F3 material (S-NVPF-2) was prepared by calcination at 550℃ for 7 h under a mixed atmosphere of hydrogen and argon. Example 3

[0047] A method for preparing a modified sodium vanadium fluorophosphate material includes the following steps: 0.02 mol ammonium metavanadate is added to 150 mL of deionized water, and the mixture is heated to 75 °C in a water bath and stirred at 100 rpm for 25 min; 0.02 mol oxalic acid is added, and stirring continues for 30 min; simultaneously, 0.02 mol anhydrous sodium dihydrogen phosphate and 0.03 mol sodium fluoride are added and stirred for 1 h; then, sodium hexametaphosphate powder is added at a mass ratio of 1:0.75 (the theoretical yield of sodium hexametaphosphate to NVPF, i.e., the theoretical yield of pure phase Na3V2(PO4)2F3 obtained from the above ratio), and stirring continues for 1 h to obtain a mixed solution; the uniformly stirred mixed solution is transferred to a reaction vessel with a polytetrafluoroethylene liner, and the temperature is raised to 170 °C for 9 h; the reaction product is washed three times each with anhydrous ethanol and deionized water, and then dried at 85 °C for 12 h; the dried reaction product is then subjected to a reaction in a solution containing 2 vol Modified Na3V2(PO4)2F3 material (S-NVPF-3) was prepared by calcination at 550℃ for 7 h under a mixed atmosphere of hydrogen and argon. Example 4

[0048] A method for preparing a modified sodium vanadium fluorophosphate material includes the following steps: 0.02 mol ammonium metavanadate is added to 150 mL of deionized water, and the mixture is heated to 75 °C in a water bath and stirred at 100 rpm for 25 min; 0.02 mol oxalic acid is added, and stirring is continued for 30 min; simultaneously, 0.02 mol anhydrous sodium dihydrogen phosphate and 0.03 mol sodium fluoride are added and stirred for 1 h; then, sodium hexametaphosphate powder is added at a mass ratio of 1:0.75 between the amount of sodium hexametaphosphate added and the theoretical yield of NVPF (i.e., the theoretical yield of pure phase Na3V2(PO4)2F3 obtained from the above ratio), and stirring is continued for 1 h to obtain a mixed solution; the above uniformly stirred mixed solution is transferred to a reaction vessel with a polytetrafluoroethylene liner, and the temperature is raised to 180 °C for 10 h; the reaction product is washed three times each with anhydrous ethanol and deionized water, and then dried at 85 °C for 12 h; the dried reaction product is then subjected to a reaction containing 2 vol Modified Na3V2(PO4)2F3 material was obtained by calcining at 550°C for 7 h in a mixed atmosphere of hydrogen and argon, proving that the modified Na3V2(PO4)2F3 material of the present invention can still be obtained by controlling the hydrothermal temperature. Comparative Example 1

[0049] A method for preparing sodium vanadium fluorophosphate material includes the following steps: 0.02 mol ammonium metavanadate is added to 150 mL of deionized water, and the mixture is heated to 75 °C in a water bath and stirred at 100 rpm for 25 min; 0.02 mol oxalic acid is added, and stirring is continued for 30 min; simultaneously, 0.02 mol anhydrous sodium dihydrogen phosphate and 0.03 mol sodium fluoride are added and stirred for 1 h to obtain a mixed solution; the above uniformly stirred mixed solution is transferred to a reaction vessel with a polytetrafluoroethylene liner, and the temperature is raised to 170 °C for 9 h; the reaction product is washed three times each with anhydrous ethanol and deionized water, and then dried at 85 °C for 12 h; the dried reaction product is calcined at 550 °C for 7 h under an argon mixed atmosphere containing 2 vol% hydrogen to obtain Na3V2(PO4)2F3 material (B-NVPF). Comparative Example 2

[0050] A method for preparing sodium vanadium fluorophosphate material includes the following steps: 0.02 mol ammonium metavanadate is added to 150 mL of deionized water, and the mixture is heated to 75 °C in a water bath and stirred at 100 rpm for 25 min; 0.02 mol oxalic acid is added, and stirring is continued for 30 min; simultaneously, 0.02 mol anhydrous sodium dihydrogen phosphate and 0.03 mol sodium fluoride are added and stirred for 1 h to obtain a mixed solution; the above uniformly stirred mixed solution is transferred to a reaction vessel with a polytetrafluoroethylene liner, and the temperature is raised to 170 °C for 9 h; the reaction product is washed three times each with anhydrous ethanol and deionized water, and then dried at 85 °C for 12 h; the dried reaction product is calcined at 550 °C for 7 h under an argon mixed atmosphere containing 2 vol% hydrogen to obtain Na3V2(PO4)2F3 material (B-NVPF). B-NVPF was then mixed with polyamide (PA) (used here as a char-forming agent) at a mass ratio of 10:1. The mixture was ball-milled at 450 r / min for 12 h. The resulting mixture was washed three times with anhydrous ethanol, then heated to 90 °C and dried for 12 h. Finally, it was sintered at 600 °C for 4 h in an argon atmosphere containing 2 vol % hydrogen to obtain B-NVPF@C. Comparative Example 3

[0051] A method for preparing sodium vanadium fluorophosphate material includes the following steps: 0.02 mol ammonium metavanadate is added to 150 mL of deionized water, and the mixture is heated to 75 °C in a water bath and stirred at 100 rpm for 25 min; 0.02 mol oxalic acid is added, and stirring is continued for 30 min; simultaneously, 0.02 mol anhydrous sodium dihydrogen phosphate and 0.03 mol sodium fluoride are added and stirred for 1 h; then, sodium hexametaphosphate powder is added at a mass ratio of 1:0.5 (the theoretical yield of sodium hexametaphosphate to NVPF, i.e., the theoretical yield of pure phase Na3V2(PO4)2F3 obtained from the above ratio), and stirring is continued for 1 h to obtain a mixed solution; the uniformly stirred mixed solution is transferred to a reaction vessel with a polytetrafluoroethylene liner and heated to 170 °C for 9 h; the reaction product is washed three times each with anhydrous ethanol and deionized water, and then dried at 85 °C for 12 h; the dried reaction product is calcined at 550 °C for 7 h under an argon atmosphere containing 2% hydrogen. Modified Na3V2(PO4)2F3 material (S-NVPF-2) was prepared by [method name missing]. S-NVPF-2 was then mixed with polyamide (used as a char-forming agent) at a mass ratio of 10:1. The mixture was ball-milled at 450 r / min for 12 h. The resulting mixture was washed three times with anhydrous ethanol, then heated to 90 °C and dried for 12 h. Finally, it was sintered at 600 °C for 4 h in an argon atmosphere containing 2% hydrogen to obtain S-NVPF@C15.

[0052] Performance Characterization The microstructure of S-NVPF-1, S-NVPF-2, S-NVPF-3, and B-NVPF obtained in Examples 1, 2, 3, and Comparative Example 1 was characterized, and the results are as follows: Figure 1 As shown, the NVPF crystal size gradually decreases with increasing SHMP addition. The EDS elemental distribution diagram shows that Na, V, P, O, and F elements are uniformly distributed on S-NVPF-2, indicating that modified NVPF has been successfully synthesized without significant elemental segregation.

[0053] The S-NVPF-1, S-NVPF-2, S-NVPF-3, and B-NVPF prepared in Examples 1, 2, 3, and Comparative Example 1 were assembled into sodium-ion batteries for cycle stability testing. The test voltage window was 2.0-4.5V, and the test temperature was 30℃. The test results are as follows: Figure 2 As shown. Cycling performance at 0.5 C medium rate for 100 cycles: The first-cycle discharge specific capacities of the four samples, B-NVPF, S-NVPF-1, S-NVPF-2, and S-NVPF-3, are 100.79, 95.1, 106.4, and 95.99 mAh·g, respectively. -1 After 100 cycles, the capacity retention rates of the samples were 89.2%, 94.2%, 96.9% and 95.4%, respectively. Among them, the S-NVPF-2 electrode has the highest first-cycle discharge specific capacity and the best cycle stability, showing significant performance advantages.

[0054] like Figure 3 As shown, the discharge specific capacity data of the S-NVPF-2 electrode during 1 C cycling at cycles 1, 2, 50, 70, 100, and 200 are 113.34, 111.29, 109.56, 106.01, 104.55, and 102.75 mAh·g, respectively. -1 The capacity exhibits a slow and steady decay trend, further confirming its structural stability. Furthermore, the charge-discharge curves of the S-NVPF-2 electrode reveal two pairs of redox plateaus (-3.7 V, -4.2 V) characteristic of NVPF materials, demonstrating that the S-NVPF-2 electrode material possesses the correct NVPF crystal structure, the expected electrode electrochemical reaction, and that the electrode fabrication process did not impair its intrinsic electrochemical activity.

[0055] Figure 4 These are the performance curves of B-NVPF, S-NVPF-2, and S-NVPF@C15 electrodes after 100 cycles at 0.5 C. The first-cycle discharge specific capacities of the three electrode groups are 100.79, 106.4, and 113.08 mAh·g, respectively. -1After 100 cycles, the capacity retention rates were 89.2%, 97.5%, and 96.3%, respectively. Overall, S-NVPF@C15 exhibited better cycle stability while maintaining a high discharge specific capacity, proving that combining SHMP particle size control with carbon coating can effectively improve the cycle discharge capacity and stability of NVPF.

[0056] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, and not all embodiments. People can obtain other embodiments based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A modified sodium vanadium fluorophosphate material, characterized in that, It includes a sodium vanadium fluorophosphate matrix and sodium hexametaphosphate adsorbed on the surface of the sodium vanadium fluorophosphate matrix, wherein the mass ratio of sodium hexametaphosphate to the sodium vanadium fluorophosphate matrix is ​​1:(0.25-0.75).

2. The modified sodium vanadium fluorophosphate material according to claim 1, characterized in that, The sodium vanadium fluorophosphate matrix is ​​composed of ammonium metavanadate, oxalic acid, anhydrous sodium dihydrogen phosphate, and sodium fluoride in a molar ratio of N. 偏钒酸铵 :N 草酸 :N 无水磷酸二氢钠 :N 氟化钠 Made with a ratio of 2:2:2:

3.

3. The method for preparing a modified sodium vanadium fluorophosphate material according to claim 1 or 2, characterized in that, Includes the following steps: (1) Preparation of precursor: Ammonium metavanadate was dissolved in deionized water and stirred at 70-80℃ and 80-120 rpm for 20-30 min; oxalic acid was added and stirring was continued for 25-35 min to obtain a blue solution; anhydrous sodium dihydrogen phosphate and sodium fluoride were added and stirred for 0.8-1.2 h; sodium hexametaphosphate was added and stirring was continued for 0.8-1.2 h to obtain the precursor solution; (2) Hydrothermal reaction: The precursor solution obtained in step (1) is transferred to a reaction vessel with a polytetrafluoroethylene liner, and the temperature is raised to 170-180℃ for 9-10 h to obtain the reaction product; (3) Post-processing: The reaction product obtained in step (2) is centrifuged, washed, dried and ground, and then calcined at 540-560℃ for 6.5-7.5h in a hydrogen-containing argon mixed atmosphere.

4. The method for preparing a modified sodium vanadium fluorophosphate material according to claim 3, characterized in that, In step (1), ammonium metavanadate is first dissolved in deionized water and stirred at 75 °C at 100 rpm for 25 min. Then oxalic acid is added and stirred at 75 °C for 30 min. Then anhydrous sodium dihydrogen phosphate and sodium fluoride are added and stirred for 1 hour. Then sodium hexametaphosphate is added and stirred for 1 hour.

5. The method for preparing a modified sodium vanadium fluorophosphate material according to claim 3, characterized in that, The centrifugal cleaning in step (3) involves washing with anhydrous ethanol 2-3 times, followed by washing with deionized water 2-3 times; the drying involves drying at 85-95℃ for 11-13 hours; and the grinding involves grinding with an agate mortar for 10-14 hours.

6. A modified sodium vanadium fluorophosphate composite material, characterized in that, It includes the modified sodium vanadium fluorophosphate material according to claim 1 or 2 and a carbonizing agent coated on its surface, wherein the mass content of the carbonizing agent is 5-15%.

7. The method for preparing a modified sodium vanadium fluorophosphate composite material according to claim 6, characterized in that, The char-forming agent is at least one of polyamide, polypyrrole, polyaniline, sucrose, or citric acid.

8. The method for preparing a modified sodium vanadium fluorophosphate composite material according to claim 7, characterized in that, The steps include the following: (1) The modified sodium vanadium fluorophosphate material and the carbonizing agent are mixed at a mass ratio of 10:(0.5-1.5) and ball-milled for 8-14 hours to obtain a mixture; (2) After cleaning and drying the mixture obtained in step (1), sinter it at 580-620℃ for 3.5-4.5h in a hydrogen-containing argon mixed atmosphere.

9. A sodium-ion battery cathode material, characterized in that, It includes the modified sodium vanadium fluorophosphate composite material according to claim 7, a conductive agent, and a binder, wherein the mass content of the modified sodium vanadium fluorophosphate composite material is 60-90%.

10. A sodium-ion battery cathode material according to claim 9, characterized in that, The mass ratio of the modified sodium vanadium fluorophosphate composite material, the conductive agent, and the binder is (7-8):(1-2):(1-2).

Citation Information

Patent Citations

  • Method for controllably preparing vanadium sodium fluorophosphate positive electrode material

    CN108682855A